(untitled) (Universal International Scientific Journal, 2026)
In socio-economic conditions, the problem of the formation of a young specialist, who is a direct producer of material goods on the basis of market relations and a significant element in the formation of professional and cultural potential in the country, is of particular importance. The level of formation of the personality becomes one of the conditions for the development of both production and social relations. In accordance with the requirements of scientific and technical progress, a multi-directional orientation of the specialist’s personality and multi-level professional training are necessary. The article discusses the professional educational activities of future teachers of technological education.